Tourism Village Development Strategy Anjir Muara District, Barito Kuala Regency - Sophia, Nurhaliza; Alviawati, Eva; Saputra, Aswin Nur; Arisanty, Deasy; Hastuti, Karunia Puji (Universitas Lambung Mangkurat, 2024)
The problem with tourism development is that local village communities have not been able to utilize and manage the potential of existing resources as potential for the tourist village, so that tourism activities or activities in the area have not been able to provide tourists with an experience that is identical to the tourist village. This research aims to analyze development strategies that are appropriate to the conditions in the Anjir Muara District Tourism Village. This research uses a quantitative approach to describe the problems and focus of this research. The sampling technique in the Anjir Muara District Tourism Village used Accidental Sampling. Researchers use this technique to take samples based on chance, so that researchers are able to take samples of anyone they meet at the research location without prior planning. The sample used in this research was 96 respondents. The data analysis used is SWOT analysis to determine development strategies that suit existing conditions in the Anjir Muara District Tourism Village. From the research results, it can be seen that one of the development strategies that suits the conditions of the Marabahan Baru Tourism Village is to develop agrotourism by showing the farming culture of the local community. One of the development strategies that is appropriate to the conditions of the Anjir Serapat Muara Tourism Village is to develop existing river tourism activities, such as creating tour packages around the tourist village including mangrove parks and local fruit gardens to make tourism activities unique and different from other tourism in the area. surroundings. Meanwhile, a development strategy that is appropriate to the conditions of the Anjir Serapat Muara I Tourism Village is to utilize easy access to the pier in Anjir Serapat Muara I Village to offer air transportation services to the local community.